Can ferrroelasticity be evaluated by nanoindentation?. Issue 13 (October 2018) - Araki, Wakako; Wang, Xin; Atkinson, Alan
Abstract: The present study investigated the possibility of evaluating ferroelastic mechanical characteristics by spherical indentation. Finite element simulation of spherical indentation, with a relatively large sphere, of a ferroelastic-plastic material was performed using characteristic bulk data of a typical ferroelastic oxide (LaSrCoFeO). The simulation results showed that the ferroelastic mechanical behaviour cannot be observed in the indentation load vs depth curve, but is clearly observable in the indentation stress vs indentation strain curve, which can be obtained reliably in experiments by estimating the contact radius using load-partial unloading sequences. The method can be reliable when the indentation stress is under the upper ferroelastic critical stress. Therefore, in principle ferroelastic mechanical characteristics could be evaluated by spherical indentation by obtaining the indentation stress vs indentation strain curve using partial unloading to estimate the contact radius, although the requirements are very difficult to satisfy in actual experiments.